Pain and its Treatment in Christian Philosophy "Augustine and Thomas Aquinas as Models" - Ass.Lect Kazem Lafteh Jabr (Journal of College of Education, 2026)
Pain is an existential concept that is inseparable from the life and formation of every human being. The value of pain is linked to higher values ​​(truth, goodness, and beauty), as well as to the meaning of religion, psychological conditions, social customs and traditions, and political ideologies. Pain, as a concept, is relative among individuals.Pain is one of the important existential questions that has occupied philosophical thought since the earliest days of rational thought. This question is of great importance in Christian philosophy, as it raises issues surrounding the suffering of life, torment, and the relationship between man and God. Through the teachings of the Christian religion, pain is viewed as a spiritual and moral human experience linked to evil, sacrifice, and salvation, transcending biological and psychological dimensions. Therefore, the philosophy of both Augustine and Thomas Aquinas was based on the study of pain to understand the relationship between man and himself, or between man and his Creator. Their understanding of pain was not limited to rational interpretation only, but they sought to understand it through the Holy Bible and philosophical thought.
Keywords: pain, therapy, philosophy, Christianity .